Stand-alone Solar Monitoring System using Internet of Things for Fertigation System - Abdullah, Mohd Noor; Sapuan, Izyan (Evolution in Electrical and Electronic Engineering, 2020)
This paper present the development of a solar photovoltaic (PV) monitoring system and design the stand-alone solar PV system for the fertigation system. With the implementation of the Internet of Things (IoT), users can monitor the performance of the solar system through the Blynk application. The parameters involved for the evaluation of the solar panel’s performance including the voltage, current, power, temperature, and dust density. Arduino Mega as the microcontroller for the sensors has been connected with the NodeMCU ESP8266 device as a medium to communicate between the microcontroller and the Blynk application. As a result, the data from the sensors are collected and displayed on the mobile phone in real-time, thus capable to evaluate the performance of the solar PV system for the fertigation system.